Method for discovering novel DNA viruses in blood using viral particle selection and shotgun sequencing - Mya Breitbart; Forest Rohwer (BioTechniques)
Rapid identification of viruses is needed to monitor the blood supply for emerging threats. Here we present a method that meets these criteria and allows for the shotgun sequencing of novel, uncultured DNA viruses directly from human blood. This method employs selection based on the physical properties of viruses combined with sequence-independent amplification and cloning. We show that both single- and double-stranded DNA viruses can be recovered from blood samples using this approach. In addition, we report the discovery of novel anellovirus sequences in the blood of healthy donors. PCR primers designed to amplify these novel anellovirus sequences were then used to verify the presence of these viruses in the general donor population.